UBERIZATION AND WORKING CONDITIONS OF DRIVERS AT COP30: BETWEEN PRECARIOUSNESS AND INCOME OPPORTUNITY - Almeida, Ruth Helena Cristo; da Silva, Aylla Maria Mendes; de Oliveira, Denise Sousa; Fonseca, Dayane Sebastiana da Costa Pedrosa; dos Santos, Manoely Lima; Nassar, Carina Leal (Seven Editora, 2025)
This research investigated how uberization, a work model mediated by apps, intensified during COP30 in Belém. To this end, books, scientific articles, reports from national and international institutions, and news about mobility and mega-events were analyzed. Authors such as Ricardo Antunes, Ludmila Abílio, and Porto-Gonçalves were studied, in addition to documents from the ILO, IBGE, IPEA, and reports from previous COPs. The analysis followed Bardin’s method (2011), allowing the material to be organized into themes such as precariousness, social inclusion, informality, and the economic impacts of mega-events. The results show that COP30 may have generated a temporary increase in income for app drivers, but it also reinforced inequalities and the absence of labor rights. Thus, the event exposes the contrast between economic opportunity and the precariousness of work, especially for the most vulnerable groups in urban Amazonia. DOI: https://doi.org/10.56238/sevened2025.040-011